2016
DOI: 10.15430/jcp.2016.21.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Reactive Oxygen Species in Apoptosis

Abstract: Generation of reactive oxygen species (ROS) by diverse anti-cancer drugs or phytochemicals has been closely related with the induction of apoptosis in cancers. Also, the downregulation of ROS by these chemicals has been found to block initiation of carcinogenesis. Therefore, modulation of ROS by phytochemicals emerges as a crucial mechanism to regulate apoptosis in cancer prevention or therapy. This review summarizes the current understanding of the selected chemical compounds and related cellular components t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 84 publications
2
54
0
Order By: Relevance
“…43,44 The increase of ROSs is often observed in cell apoptosis progress and the upregulation of ROSs can be an indication of apoptosis. 45 In our study, we discovered a down-regulation of ROS levels when we overexpressed CD38. This indicates that CD38 may inhibit cell apoptosis in cervical cancer cells via influence on ROS levels.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…43,44 The increase of ROSs is often observed in cell apoptosis progress and the upregulation of ROSs can be an indication of apoptosis. 45 In our study, we discovered a down-regulation of ROS levels when we overexpressed CD38. This indicates that CD38 may inhibit cell apoptosis in cervical cancer cells via influence on ROS levels.…”
Section: Discussionmentioning
confidence: 53%
“…Besides, reactive oxygen species (ROSs) play a vital role in numerous cellular biological activities including proliferation, apoptosis, and metastasis . The increase of ROSs is often observed in cell apoptosis progress and the upregulation of ROSs can be an indication of apoptosis . In our study, we discovered a down‐regulation of ROS levels when we overexpressed CD38.…”
Section: Discussionmentioning
confidence: 59%
“…Supplementation with quercetin, resveratrol or vitamin C during in vitro maturation might act as a defence mechanism against ROS and also may contribute to maintain the GSH system (Jeong & Joo, ; Kovacic & Somanathan, ; Padayatty et al., ; Wang et al., ). However, even with reduction in intracellular ROS levels with these antioxidants, which was detected in the present study, increase in GSH levels was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with quercetin, resveratrol or vitamin C during in vitro maturation might act as a defence mechanism against ROS and also may contribute to maintain the GSH system (Jeong & Joo, 2016;Kovacic & Somanathan, 2010;Padayatty et al, 2003;Wang et al, 2014).…”
Section: Some Antioxidants Have Direct Actions On Ros Contributing Withmentioning
confidence: 99%
See 1 more Smart Citation